Expression of eukaryotic initiation factor 5A and hypusine forming enzymes in glioblastoma patient samples: implications for new targeted therapies. - Michael Preukschas; Christian Hagel; Alexander Schulte; Kristoffer Weber; Katrin Lamszus; Henning Sievert; Nora Pällmann; Carsten Bokemeyer; Joachim Hauber; Melanie Braig; Stefan Balabanov (PLoS ONE, 2012)
Glioblastomas are highly aggressive brain tumors of adults with poor clinical outcome. Despite a broad range of new and more specific treatment strategies, therapy of glioblastomas remains challenging and tumors relapse in all cases. Recent work demonstrated that the posttranslational hypusine modification of the eukaryotic initiation factor 5A (eIF-5A) is a crucial regulator of cell proliferation, differentiation and an important factor in tumor formation, progression and maintenance. Here we report that eIF-5A as well as the hypusine-forming enzymes deoxyhypusine synthase (DHS) and deoxyhypusine hydroxylase (DOHH) are highly overexpressed in glioblastoma patient samples. Importantly, targeting eIF-5A and its hypusine modification with GC7, a specific DHS-inhibitor, showed a strong antiproliferative effect in glioblastoma cell lines in vitro, while normal human astrocytes were not affected. Furthermore, we identified p53 dependent premature senescence, a permanent cell cycle arrest, as the primary outcome in U87-MG cells after treatment with GC7. Strikingly, combined treatment with clinically relevant alkylating agents and GC7 had an additive antiproliferative effect in glioblastoma cell lines. In addition, stable knockdown of eIF-5A and DHS by short hairpin RNA (shRNA) could mimic the antiproliferative effects of GC7. These findings suggest that pharmacological inhibition of eIF-5A may represent a novel concept to treat glioblastomas and may help to substantially improve the clinical course of this tumor entity.